Conceptualizing the characteristics of moderate Muslims: a systematic review. (1st November 2020) - Ab Rashid, Radzuwan; Fazal, Syed Ali; Ab. Halim, Zulazhan; Mat Isa, Nasharudin; Mohamad Yusoff, Zuraidah Juliana; Musa, Razali; Hamzah, Mohd Isa
ABSTRACT: Following the 9/11 terror attacks, public discourse on Islam worldwide has been characterized by the distinction between radical and moderate Muslims. In this context, moderate Muslims can play a significant role in international relations and promote moderate practice in global politics. In order to address the conceptual ambiguities and enhance our understanding of acceptable Islam, this study undertook a critical review of the term Moderate Muslim and the characteristics that could be associated with this description. A systematic search of the existing literature was conducted through the relevant scientific databases of 'Scopus' and 'Web of Science' using the keywords: 'moderate Muslim', 'moderate Islam', and 'acceptable Islam'. The search resulted in 319 articles published between the years 2001 and 2018. Following a critical analysis, 29 publications were then used to identify the characteristics of Moderate Muslims. The findings revealed that practicing Acceptable Islam, with embedded traits of non-violence and liberalism, followed by the belief in democratic, secular, and pluralist methods coupled with a spirit of tolerance is what makes (or at least is expected of) a Moderate Muslim. It is hoped that apart from extending the theoretical body of knowledge of this label, this study will also contribute to the ongoing debate about what it means to be moderate, from diverse perspectives adopted by various scholars.